2013
DOI: 10.12968/bjon.2013.22.5.277
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-oesophageal reflux. Part 2: medical treatment

Abstract: Nurses need to be aware of the effectiveness and use of these medications so that patients can make informed treatment choices and develop a greater understanding of the importance of concordance with prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The dose recommended by WHO for ranitidine is 150 mg tablet containing ranitidine base, given as the hydrochloride salt [4,11]. Twice-daily treatment with ranitidine 150 mg is a valuable therapy for GERD in a typical family practice setting and reduces the frequency and severity of symptoms within the first 24 to 48 hours of treatment [12]. Another study conducted in Oman showed that different brands of ranitidine Modern Chemistry & Applications available in market that pharmaceutical equivalent with a slight difference in manufacturing process [13].…”
Section: Introductionmentioning
confidence: 99%
“…The dose recommended by WHO for ranitidine is 150 mg tablet containing ranitidine base, given as the hydrochloride salt [4,11]. Twice-daily treatment with ranitidine 150 mg is a valuable therapy for GERD in a typical family practice setting and reduces the frequency and severity of symptoms within the first 24 to 48 hours of treatment [12]. Another study conducted in Oman showed that different brands of ranitidine Modern Chemistry & Applications available in market that pharmaceutical equivalent with a slight difference in manufacturing process [13].…”
Section: Introductionmentioning
confidence: 99%